2015
DOI: 10.1371/journal.pone.0124403
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Survey of Bacterial Communities Associated with Bacterial Chondronecrosis with Osteomyelitis (BCO) in Broilers

Abstract: Bacterial chondronecrosis with osteomyelitis (BCO) is recognized as an important cause of lameness in commercial broiler chickens (meat-type chickens). Relatively little is known about the microbial communities associated with BCO. This study was conducted to increase our understanding of the microbial factors associated with BCO using a culture-independent approach. Using Illumina sequencing of the hyper-variable region V6 in the 16S rRNA gene, we characterized the bacterial communities in 97 femoral or tibia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 57 publications
5
29
0
Order By: Relevance
“…Several factors could explain the variation in the incidence of lameness among studies, including unintentional pathogen exposure (from water lines, litter, hatchery, breeders, farm environment), diet composition (final body weights of the animals), diet contaminants (mycotoxins), and genetic lines of the animals [6,32]. Consistent with other studies [8], we found a large proportion of birds that did not show evident signs of lameness even in the presence of advanced necrotic lesions in their bones, highlighting the relevance of the subclinical presentation of BCO [39]. Staphylococcus, Salmonella, and Enterococcus are among the genera of bacteria that are most commonly isolated from BCO lesions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Several factors could explain the variation in the incidence of lameness among studies, including unintentional pathogen exposure (from water lines, litter, hatchery, breeders, farm environment), diet composition (final body weights of the animals), diet contaminants (mycotoxins), and genetic lines of the animals [6,32]. Consistent with other studies [8], we found a large proportion of birds that did not show evident signs of lameness even in the presence of advanced necrotic lesions in their bones, highlighting the relevance of the subclinical presentation of BCO [39]. Staphylococcus, Salmonella, and Enterococcus are among the genera of bacteria that are most commonly isolated from BCO lesions.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, even though lower body weights do not support the development of skeletal microfractures in the ramp model, circulating bacteria may be able to migrate through the fenestrated capillaries of the skeletal system and remain attached to the cartilage matrix of young birds until the microfractures develop, which then provide a perfect niche for bacterial growth at an older age. In fact, using molecular techniques, bacteria can be found in the bones of healthy birds on a regular basis [39]. In our studies, the high incidence of BCO suggests that bacterial translocation occurred at some point in the life of the animals, regardless of the lesions generated by the SNE challenge.…”
Section: Discussionmentioning
confidence: 52%
“…It should be noted that in those birds where were able to culture bacteria from apparently healthy femora and tibiae, they were negative for culture of bacteria from blood so the presence of the bacteria in the bone is not from a general sepsis. Previous metagenomics work published by our collaborators, has already shown that DNAs of many bacterial genera can be detected in apparently healthy proximal femorae and tibia [ 28 ]. As these experiments utilized chicks obtained from a commercial hatchery we hypothesized that they could have been contaminated with S .…”
Section: Resultsmentioning
confidence: 99%
“…Macroscopic lesions in brain tissues following the injection of partridges were mostly inapparent, but the histopathological examination of the brain tissue revealed congestion and thrombosis. Experimentally induced staphylococcosis as well as naturally occurring disease have been reported in chickens (Mutalib et al 1983a, McNamee et al 2000, Jiang et al 2015, turkeys (Linares et al 2001, Corrand et al 2012, pet birds (Briscoe et al 2008, Huynh et al 2014, Iverson et al 2015, birds of prey (Poorbaghi et al 2012, Bezjian 2014, waterfowl (Degernes et al 2011, Mondal et al 2014, and other avian species (Lemon et al 2012). The pathogenesis of systemic infection with Staphylococcus aureus in chukar partridge chicks is not clearly defined.…”
Section: Discussionmentioning
confidence: 99%